Evaluasi Keberhasilan Sistem Keuangan Desa Menggunakan Delone & Mclean Is Succes Model - Nabilla Utmary; Henri Agustin (Universitas Negeri Padang, 2020)
This study aims to evaluate the implementation of the Rural Financial System (Sistem Keuangan Desa or SISKEUDES). It also seeks to identify the factors that may effect the user satisfaction and actual use of SISKEUDES at the 55 villages in Pariaman City. The data used in this research is primary data obtained by spread the questionnaires to each villages government. This study using purposive sampling with a sample of 55 village tresuers/SISKEUDES operators. Data analysis technique using SmartPLS ver3.0 processed This study found that information quality has a positive effect on user satisfaction, and system quality, service quality has not effect on user satisfaction, while, user satisfaction also has not effect on actual use of SISKEUDES.